PENGARUH LATIHAN POWER OTOT LENGAN TERHADAP KEMAMPUAN CHEST PASS BOLA BASKET SMP TRI BHAKTI PEKANBARU - M. Fransazeli Makorohim (Universitas Negeri Semarang, 2016)
This study aims to find out about how much influence of muscle power training arm of the ability of basketball Chest passjunior high school students' extracurricular son of tri bhakti pekanbaru. This study is an experiment that uses the Chest pass test before and after exercise. The study was conducted of Tri Bhakti Pekanbaru. The research data gathered through the data Pree and post test and treated with t-test technique. The analysis shows encountered in the study between Pree test and post test students' ability to Chest pass significance level). Based on these data it is clear that the alternative hypothesis is accepted that are significant influence of muscle power training arm of the ability of basketball Chest pass junior high school students' extracurricular Tri Bhakti Pekanbaru. Thus the results of research done to say that exercise variation influence of muscle power training arm of the ability of basketball Chest pass junior high school students' extracurricular of Tri Bhakti Pekanbaru.